2017
DOI: 10.1103/physrevb.96.094530
|View full text |Cite
|
Sign up to set email alerts
|

Larkin-Ovchinnikov state of superconducting Weyl metals: Fundamental differences between restricted and extended pairings in k -space

Abstract: Two common approaches of studying theoretically the property of a superconductor are shown to have significant differences, when they are applied to the Larkin-Ovchinnikov state of Weyl metals. In the first approach the pairing term is restricted by a cutoff energy to the neighborhood of the Fermi surface, whereas in the second approach the pairing term is extended to the whole Brillouin zone. We explore their difference by considering two minimal models for the Weyl metal. For a model giving a single pair of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…However, due to the effective doubling of degrees of freedom, induced by pairing, which is corrected by the factor of 1/2 in Eq. ( 6), the Fermi arc get copied to the part of the BZ outside of the Weyl points, and occupies the range of 4Q, which always coincides with the size of the new BZ, reduced by the translational symmetry breaking in the FFLO state [40]. When Q = G/4, however, this range is identical to the size of the original BZ, which is another way to see why the FFLO state does not break translational symmetry when and only when the Weyl node separation is exactly half the size of the BZ [15].…”
mentioning
confidence: 99%
“…However, due to the effective doubling of degrees of freedom, induced by pairing, which is corrected by the factor of 1/2 in Eq. ( 6), the Fermi arc get copied to the part of the BZ outside of the Weyl points, and occupies the range of 4Q, which always coincides with the size of the new BZ, reduced by the translational symmetry breaking in the FFLO state [40]. When Q = G/4, however, this range is identical to the size of the original BZ, which is another way to see why the FFLO state does not break translational symmetry when and only when the Weyl node separation is exactly half the size of the BZ [15].…”
mentioning
confidence: 99%
“…This may lead to unconventional superconducting states, such as a mixed singlet and triplet superconductivity [35][36][37] , or a Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) finite momentum pairing [38][39][40][41][42][43] . It can also enable the realization of a Weyl semimetal phase, which, coupled to superconductivity, constitutes an ideal platform to study unconventional superconducting states or topological superconductivity [44][45][46][47][48][49][50][51] .…”
Section: Introductionmentioning
confidence: 99%
“…The superconducting transition temperature is about 0.5 K. However, a recent study showed that it is a superconducting Weyl semimetal with nodal points [7]. The superconductivity in doped WSMs [1][2][3][8][9][10][11][12][13] has become a topic of interest in unconventional superconductivity. Theoretically, for the lightly doped Weyl semimetal, the Fermi energy is sufficiently close to the Weyl nodes such that the Fermi surface consists of an even number of disconnected Fermi sheets around the Weyl nodes.…”
Section: Introductionmentioning
confidence: 99%